Medicine use in surgery risk patients and repercussion in Dentistry - Maribel Bastarrechea Milián; Ileana Quiñones La Rosa (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: With the growing of population aging, the dental practice requires the adequate knowledge to identify and treat patients with increasingly frequent systemic diseases, which may require the use of drugs capable of interacting with the pharmacological treatment of their underlying diseases. The literature reflects this relationship in a fragmented manner and lacking a systemic approach. Objective: To identify the drugs used in risk patients undergoing surgery and describe their repercussion during dental treatment. Material and Method: A bibliographic review was carried out.  Scientific articles, specialists´ theses, Master´s and PhD degrees among other references were consulted, mainly the ones obtained from the search carried out in Google during the last 5 years. Results: The generalities, dental management and drug interactions between the diseases studied (diabetes mellitus, arterial hypertension and heart disease) were addressed, as well as the situations that require antibiotic prophylaxis. Conclusions: The surgical risk patients studied use drugs that produce important interactions with drugs such as NSAIDs, local anesthetics and glucocorticoids that are usually used in dental treatments.  There are also systemic diseases in which antibiotic prophylaxis must be taken into account before performing certain dental procedures. Keywords: Surgical risk, systemic diseases, drugs used in dental treatments, antibiotic prophylaxis.